1974
DOI: 10.1029/jb079i002p00332
|View full text |Cite
|
Sign up to set email alerts
|

Quartz to stishovite: Wave propagation in the mixed phase region

Abstract: This work reports on phase transition kinetics and wave propagation in Arkansas novaculite, a fine‐grained polycrystalline α quartz rock, when it is subject to high‐pressure dynamic loading and relief. The stress region studied is between 150 and 400 kbar, where the polymorphic phase transition from α quartz to stishovite is believed to occur. Particular emphasis was focused on the unloading behavior in the mixed phase region. High‐pressure loading is provided by conventional explosive methods. Measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 18 publications
3
51
0
Order By: Relevance
“…Based on earlier studies (Grady et al, 1974) on a similar density quartz rock, an elastic shock velocity of 6.2 km/s was assumed in order to perform Hugoniot analysis on the present compressive shock-waves.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…Based on earlier studies (Grady et al, 1974) on a similar density quartz rock, an elastic shock velocity of 6.2 km/s was assumed in order to perform Hugoniot analysis on the present compressive shock-waves.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…It is deduced that diaplectic glass very likely forms after the compressional stage, during pressure release. Experimental studies of Ahrens et al (I969) and Grady et al (1974) on quartz, and Grady and Murri (1976) on feldspars show that a high-to-low density phase transition effectively occurs in some portion of the shocked constituents during pressure release. It can be concluded that fractures are formed at the end of the shock sequence, very likely during pressure release or after.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts were undertaken to alleviate (or at least minimize) such gauge concerns. Perhaps most convincing was concurrent shock studies on quartz rock [7]. Comparable pressure level profiles in quartz exhibited no anomalous behavior.…”
Section: Structured Shock Waves In Dolomitementioning
confidence: 82%